Study on the Status Quo of Smart Campus Construction in Higher Vocational Colleges: The Case of Z School of China’s Guangdong Province - Deng, Zhaoxi; Badiane , Kemo (International Journal of Learning and Development, 2024)
The construction of smart campuses is an inevitable trend in the future development of major colleges, especially higher vocational colleges aiming at cultivating high-quality, high-skilled, and high-professional innovative talents. To achieve this goal, higher vocational colleges must develop education informatization, which is an inevitable choice in the new era and the background of "Internet +". Based on advanced technologies, such as cloud computing, big data, Internet+, and new artificial intelligence, combined with high-quality networks and various smart devices, digital education will be carried out to promote the transformation of traditional education to intelligent and innovative education. This article uses Z School as a case study, analyzes its application status, finds its limitations, and puts forward corresponding suggestions. It also provides reference for similar higher vocational colleges so as to promote the construction of educational information in higher vocational colleges and improve the effectiveness of quality education for higher vocational colleges.